2023
DOI: 10.3389/fpubh.2023.1139786
|View full text |Cite
|
Sign up to set email alerts
|

Associations between eHealth literacy, mental health-seeking attitude, and mental wellbeing among young electronic media users in China during the COVID-19 pandemic

Abstract: ObjectiveThis study aimed to examine the associations among mental health related eHealth literacy (eHL), mental health-seeking attitude, and wellbeing among Chinese young electronic media users during the COVID-19 pandemic.MethodsA web-based cross-sectional survey was conducted in Guangzhou, China. The modified eHealth literacy Scale, Mental Help-Seeking Attitudes Scale, and Short Warwick-Edinburgh Mental Wellbeing Scale were used. Structural equation modeling (SEM) examined the associations between them and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…Management: In view of their higher mental health literacy probably due to digital information and peer sharing, 56 it is a good practice to engage the youth as our collaborating partners in their management. Similar to other age groups, immediate management would include assessment of any immediate risks to self or others, as well as any risk of neglect or abuse.…”
Section: Model Of the Youth Mental Health Clinicmentioning
confidence: 99%
See 2 more Smart Citations
“…Management: In view of their higher mental health literacy probably due to digital information and peer sharing, 56 it is a good practice to engage the youth as our collaborating partners in their management. Similar to other age groups, immediate management would include assessment of any immediate risks to self or others, as well as any risk of neglect or abuse.…”
Section: Model Of the Youth Mental Health Clinicmentioning
confidence: 99%
“…The mutual support of peers in the road of recovery would be the mainstay for the youth with advocacy of self-sufficiency, empowerment, and peer networking, 58 while mentoring by trustworthy adults would help the youth adapt and transform the experiences of the past for their own generations. 59 45,[55][56][57][58][59] health and socialisation, similar to therapeutic communities with guidance. 18 Engagement in art and cultural activities would improve stress coping and mental health for youth.…”
Section: Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…Yang et al [ 16 ] found that high eHL was significantly associated with lower levels of depression, insomnia, and posttraumatic stress disorder in 15,000 Chinese individuals. Xu et al [ 17 ] also discovered that young people with high eHL who use web-based mental health–related information tend to have a more positive attitude toward seeking mental health services and reporting better mental well-being. Another study demonstrated that rural residents with high eHL were more willing to use telemedicine and had better health status, including mental health, at the beginning of the COVID-19 pandemic [ 18 ].…”
Section: Introductionmentioning
confidence: 99%